2016
DOI: 10.1111/nmo.12862
|View full text |Cite
|
Sign up to set email alerts
|

Neurobiology of early life stress and visceral pain: translational relevance from animal models to patient care

Abstract: To better understand the mechanisms by which sex hormones and ELS contribute to IBS, animal models have been developed to mirror complex human experiences allowing for longitudinal studies that investigate the lifelong consequences of ELS. These preclinical models have been successful in recapitulating ELS-induced visceral pain. Moreover, in female rats the influence of cycling hormones on visceral hypersensitivity resembles that seen in women with IBS. Such studies suggest that rodent models of ELS may serve … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 140 publications
(159 reference statements)
0
9
0
Order By: Relevance
“…[1][2][3][4][5][6] Risk factors for IBS include being female and exposure to chronic stress. [7][8][9][10][11] A common feature of IBS is that for many patients, their symptoms are worsened by stress and overlap with other stress disorders, including anxiety, depression, and post-traumatic stress disorder. [12][13][14][15] In support of IBS being a stress-sensitive disorder, there is experimental evidence showing abnormal hypothalamicpituitary-adrenal (HPA) axis reactivity in IBS patients as shown by a heightened HPA response to a corticotropin-releasing hormone (CRH) challenge, and an overall increase in hourly cortisol secretion in IBS compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Risk factors for IBS include being female and exposure to chronic stress. [7][8][9][10][11] A common feature of IBS is that for many patients, their symptoms are worsened by stress and overlap with other stress disorders, including anxiety, depression, and post-traumatic stress disorder. [12][13][14][15] In support of IBS being a stress-sensitive disorder, there is experimental evidence showing abnormal hypothalamicpituitary-adrenal (HPA) axis reactivity in IBS patients as shown by a heightened HPA response to a corticotropin-releasing hormone (CRH) challenge, and an overall increase in hourly cortisol secretion in IBS compared to controls.…”
Section: Introductionmentioning
confidence: 99%
“…This limitation of bedding material causes disruptions in normal maternal care similar to those exhibited by dams during the MS protocol, however, the limited nesting model does not require removal of pups from the dam at any time during the experimental paradigm. This advantage also eliminates differences in weaning weights seen in the MS model (328). Another model of ELS utilizes neonatal colonic irritation using colonic infusion of mustard oil or repeated CRD in neonates (329).…”
Section: Early Life Stress Models Of Visceral Painmentioning
confidence: 99%
“…The link for stress-induced abdominal pain in IBS is not well understood. Some evidence suggests that adverse events at different stages throughout life, and especially early life, sensitize the stress response system leading to peripheral sensitization and abnormal CNS pain processing 40 . Several imaging studies have shown altered activation patterns in brain regions involved in nociception with effects on the ACC, posterior cingulate, prefrontal cortex, insula, thalamus, and somatosensory cortex in patients with IBS in response to rectal distension 41 .…”
Section: Stress and The Gut-brain Axis: Implications In Visceral Painmentioning
confidence: 99%